Serum sodium to chloride ratio and mortality on continuous ambulatory peritoneal dialysis: a multicenter retrospective study - Jiayin You; Sijie Gu; Ning Su; Xiaoran Feng; Fenfen Peng; Qingdong Xu; Xiaojiang Zhan; Yueqiang Wen; Xiaoyang Wang; Na Tian; Xianfeng Wu; Niansong Wang (MedComm)
Abstract An imbalance in the serum sodium to chloride ratio (Na/Cl) was linked to higher mortality among heart failure patients. Nonetheless, the prognostic significance of Na/Cl in individuals undergoing peritoneal dialysis (PD) remains unexplored. This study seeks to explore the association between initial Na/Cl levels and mortality in PD patients. The study, conducted across multiple centers, included 3341 patients undergoing PD from January 1, 2005, to December 31, 2021. Patients were stratified into quartiles according to baseline Na/Cl and followed up for a median of 5.77 years. To explore the association between Na/Cl levels and mortality, we employed Cox proportional hazards models, competing risks models, and restricted cubic spline analysis. Of 3341 patients, 722 patients died, including 259 cardiovascular deaths. Following adjustments for comorbidities and multiple covariates, individuals in the highest Na/Cl quartile (>1.42) exhibited lower all‐cause mortality (hazard ratio [HR] 0.63, 95% confidence interval [CI] 0.47–0.86) and cardiovascular mortality (HR 0.38, 95% CI 0.22–0.67) compared with those in the lowest quartile (<1.33). A similar pattern was also found when Na/Cl was dealt with continuous variables. Initial levels of Na/Cl at the start of PD were negatively correlated with all‐cause mortality and cardiovascular mortality in PD patients.